CS22, a novel human enterotoxigenic Escherichia coli adhesin, is related to CS15 - Pichel, Mariana (2000)
Enterotoxigenic Escherichia coli (ETEC) expresses a broad spectrum of O:H antigens. Serogroup O20 is one of the most prevalent among the ETEC strains lacking any of the defined colonization factors (CFs), in Argentina. An O20:H− strain, ARG-3, adhered to Caco-2 cells and exhibited a thermoregulated 15.7-kDa protein band upon sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). An antiserum against this protein inhibited ARG-3 adhesion to Caco-2 cells and bound to very thin fibrilla-like structures on the bacterial surface. A 15.7-kDa protein-defective mutant failed to adhere to Caco-2 cells and lacked immunogold-labeled surface structures. The N-terminal amino acid sequence of the structural subunit showed 95% homology to that of CS15 of ETEC (former antigen 8786) and 65% homology with fimbria SEF14 of Salmonella enterica serovar Enteritidis. Nevertheless, the molecular size of ARG-3 adhesin was different from that of CS15, as revealed by SDS-PAGE and mass spectrometry. Both proteins are immunologically related, yet not identical, since an antiserum against the 15.7-kDa protein reacted solely with ARG-3 after absorption with bacteria bearing CS15. Moreover, only under low stringency conditions could DNA from strain ARG-3 be amplified by PCR using primers derived from the nfaA sequence of CS15. Thus, from the DNA sequence obtained from the ARG-3 PCR product, it could be deduced that the subunit protein differed in 30 residues from that of CS15. ARG-3 adhesin was found in 60% of the O20:H- CF-negative ETEC strains from Argentina; however, it appeared restricted to this serotype. We propose the designation CS22 for the herein identified nonfimbrial adhesin of human ETEC.